Antidepressants and age - David G. Blanchflower; Andrew J. Oswald (Institute for the Study of Labor (IZA), 2011)
Antidepressants as a commodity have been remarkably little-studied by economists. This study shows in new data for 27 European countries that 8% of people (and 10% of those middle-aged) take antidepressants each year. The probability of antidepressant use is greatest among those who are middle-aged, female, unemployed, poorly educated, and divorced or separated. A hill-shaped age pattern is found. The adjusted probability of using antidepressants reaches a peak - approximately doubling - in people's late 40s. This finding is consistent with, and provides a new and independent form of corroboration of, recent claims in the research literature that human well-being follows a U-shape through life.
urn:nbn:de:101:1-20110621445
Keywords: I1; I12; I3; I31; 330; well-being; aging; mental health; depression; happiness; Easterlin paradox